Herbal hepatotoxicity: a critical review. (5th February 2013) - Teschke, Rolf; Frenzel, Christian; Glass, Xaver; Schulze, Johannes; Eickhoff, Axel
<x xml:space="preserve">Abstract</x> This review deals with herbal hepatotoxicity, identical to herb induced liver injury (HILI), and critically summarizes the pitfalls associated with the evaluation of assumed HILI cases. Analysis of the relevant publications reveals that several dozens of different herbs and herbal products have been implicated to cause toxic liver disease, but major quality issues limit the validity of causality attribution. In most of these reports, discussions around quality specifications regarding herbal products, case data presentations and causality assessment methods prevail. Though the production of herbal drugs is under regulatory surveillance and quality aspects are normally not a matter of concern, low quality of the less regulated herbal supplements may be a critical issue considering product batch variability, impurities, adulterants and herb misidentifications. Regarding case data presentation, essential diagnostic information is often lacking, as is the use of valid and liver specific causality assessment methods that also consider alternative diseases. At present, causality is best assessed by using the Council for International Organizations of Medical Sciences scale ( CIOMS) in its original or updated form, which should primarily be applied prospectively by the treating physician when evaluating a patient rather than retrospectively by regulatory agencies. To cope with these problems, a common quality approach by manufacturers, physicians and regulatory agencies should strive for the best quality. We propose steps for improvements with impact on future cases of liver injury by herbs, herbal drugs and herbal supplements.